Laporan Kegiatan Digital Skills Data Science dan Artificial Intelligence Melalui Program Studi Independen di Startup Campus (Yayasan Bakti Achmad Zaky) - Vita Syafara Eka Putri (Universitas Muhammadiyah Surakarta, 2026)
This research discusses the MSIB program at Startup Campus (Yayasan Bakti Achmad Zaky), focusing on developing data analysis and artificial intelligence skills to face the demands of the technology industry. In job search, the research observed the benefits of data analysis to improve information about job vacancies for companies and job seekers. Learning methods involve asynchronous learning and synchronous learning methods. The overview obtained in the analysis of the dataset is to provide strategies for obtaining a high-paying job in an available company. The results that can be obtained from the dataset are starting from job positions led by sales manager, sales director, and senior data scientist job positions. This research provides an in-depth insight into the MSIB program at Startup Campus and its application in developing expertise in technology and data analysis.